A stability transition at mildly acidic pH in the alpha-hemolysin (alpha-toxin) from Staphylococcus aureus - Bortoleto, R. K.; Ward, R. J. (Elsevier B.V., 1999)
The effects of mildly acidic conditions on the free energy of unfolding (Delta G(u)(buff)) of the pore-forming alpha-hemolysin (alpha HL) from Staphylococcus aureus were assessed between pH 5.0 and 7.5 by measuring intrinsic tryptophan fluorescence, circular dichroism and elution time in size exclusion chromatography during urea denaturation, Decreasing the pH from 7.0 to 5.0 reduced the calculated Delta G(u)(buff) from 8.9 to 4.2 kcal moI(-1), which correlates with an increased rate of pore formation previously observed over the same pH range, It is proposed that the lowered surface pH of biological membranes reduces the stability of alpha HL thereby modulating the rate of pore formation. (C) 1999 Federation of European Biochemical Societies.
Keywords: alpha-hemolysin; stability transition